An increase in neuropathic complaints corresponds to the severity of central sensitization-related symptoms in women with fibromyalgia: A cross-sectional study (Annals of Medical Research, 2025)
Aim: This study aimed to investigate the relationship between central sensitization (CS)-related symptoms and neuropathic complaints in female patients with fibromyalgia (FM).Materials and Methods: Demographic and clinical variables, including disease duration, current medication, severity of pain, and the FM survey questionnaire, were all recorded. The Fibromyalgia Impact Questionnaire (FIQ) was used to assess the severity of the FM. Neuropathic complaints were investigated by the Self-Leeds Assessment of Neuropathic Symptoms and Sign (S-LANSS) and CS-related symptoms by the Central Sensitization Inventory (CSI), and patient data were compared according to the CSI severity levels. Patients with CSI scores that are at least moderate (CSI≥40) were considered to have central sensitization syndrome (CSS).Results: One hundred and forty female FM patients were included in the study. The mean (SD) S-LANSS score was calculated as 15.06 (5.61) for all patients. A total of 135 patients (96.4%) had CSS; the mean (SD) CSI-A score for all patients was 61.39 (13.03). Of them, 81.4% (n = 114) were in the very severe CSS group. There was an increase in pain intensity, FIQ, and S-LANSS scores in parallel with the severity of CS-related symptoms (p
Keywords: Central nervous system; Central nervous system sensitization; Chronic pain; Fibromyalgia